An outcome evaluation of the Home-School partnership programme - Muzire, Mufudzi (School of Management Studies, 2019)
This is an outcomes evaluation of the Home-School Partnership (HSP) programme, implemented by Wordworks, an organisation based in the Western Cape Province. The programme aims to improve language and literacy for the children between four and eight years of age. To achieve this, the programme seeks to integrate parents in the process of child learning at home. The programme sensitise parents and make them realise their important role in child development. South Africa’s averages of numeracy and literacy test scores range from 30% to 35% as presented in Annual National Assessments (2011) for Grade one to six. The low language and literacy performance in South Africa is one problem that calls for action from different stakeholders. The implementing organisation train teachers to become facilitators. The facilitators will then cascade the training to parents with children aged four to eight years. This evaluation focused on addressing three evaluation questions: 1. How do teachers (facilitators) perceive the programme to have impacted on students’ literacy learning and achievement in and out of school, in terms of participation, confidence and self-esteem? 2. To what extent has the Home-School Partnership programme managed to change parents’ attitude towards child learning and improved their involvement in child learning at home? 3. What early indications are there to suggest that the Home-School Partnership programme will be sustainable after Wordworks has fully withdrawn its support? In this evaluation, a descriptive design was used. The design employed a quantitative approach to address question one as secondary data from 90 feedback reports by teachers were analysed using Microsoft excel. The data to answer the second evaluation question was gathered through interviews with six teachers and six school management members. Data from three focus group discussions with parents was used to address evaluation question three. In analysing the data, thematic analysis was used which involved the processes of open coding in generation of themes. The results of the study revealed a positive improvement of learners’ performance on various indicators that are related to child language and literacy development. Ninety percent of the 90 sampled learners showed a positive change in at least one of the several academic assessment areas. That is, 46% of learners showed some notable improvements in writing, 32% in drawing, 31% in reading and about 30% showed some improvement in vocabulary. However, these results should be interpreted with some degree of caution as the analysis was based on subjective teachers’ perceptions. Regardless of the drawbacks of the design and data collection methods, there is a growing amount of evidence from other studies to validate the findings of this study. There were some positive changes noted in parents particularly their attitude towards child learning. Parents are now more involved in child learning and have gained some important skills to support child development. However, the results need to be taken with caution as they are based on subjective perceptions of parents. There was always an increase in the number of parents who enrolled for the programme each year and more interestingly, men started enrolling for the programme in the last two years. In 2016, a total of 42 men were trained and in 2017, a total of 86 men were trained under HSP. This provides some evidence of the ability of the HSP programme to change parents’ attitude towards child learning. The HSP programme shows some signs of sustainability particularly around environmental support and organisational domains. In this regard, results of the study revealed that the HSP programme has managed to garner support from its operational environment. The programme is particularly applauded by teachers, school leadership and parents, and their appreciation is one of the indicators of sustainability. Under organisational support, the study revealed that the teachers and parents are satisfied with the timely support they are receiving from Wordworks. However, there are some gaps around programme evaluation and funding stability domains. All the schools are still fully receiving financial support from Wordworks to facilitate the HSP programme. Based on the study findings it is prudent that Wordworks prepares schools for continuity in the event that their support is withdrawn and a more robust monitoring and evaluation system needs to be put in place. It is recommended that the programme documents more success stories to showcase its relevance.